2014
DOI: 10.2169/internalmedicine.53.0898
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations at Diagnosis in Japanese Patients with Systemic AL Amyloidosis: A Retrospective Study of 202 Cases with a Special Attention to Uncommon Symptoms

Abstract: Objective To retrospectively investigate the clinical manifestations at diagnosis in Japanese patients with systemic AL amyloidosis. Methods We reviewed the medical records of 230 Japanese patients who had visited our hospital and been diagnosed with AL amyloidosis, and abstracted those with the systemic type. The clinical data at diagnosis of systemic AL amyloidosis, including laboratory and imaging findings, were analyzed. Results Two hundred and two patients (mean, 58.7±9.5 years) were enrolled in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 51 publications
2
26
0
Order By: Relevance
“…h Amyloid deposition in the vascular wall was revealed in the lung (arrow, direct fast scarlet stain). Scale bars in a, b, d-g 400 lm; in c, h 200 lm proteinuria and/or renal dysfunction (109/202, 54.0 %), congestive heart failure (50/202, 24.8 %), peripheral neuropathy (21/202, 10.4 %), hepatomegaly (16/202, 7.9 %), and arrhythmia (10/202, 5.0 %) [6]. Five patients (2.5 %) showed GI bleeding as an initial symptom in that study.…”
Section: Discussionmentioning
confidence: 99%
“…h Amyloid deposition in the vascular wall was revealed in the lung (arrow, direct fast scarlet stain). Scale bars in a, b, d-g 400 lm; in c, h 200 lm proteinuria and/or renal dysfunction (109/202, 54.0 %), congestive heart failure (50/202, 24.8 %), peripheral neuropathy (21/202, 10.4 %), hepatomegaly (16/202, 7.9 %), and arrhythmia (10/202, 5.0 %) [6]. Five patients (2.5 %) showed GI bleeding as an initial symptom in that study.…”
Section: Discussionmentioning
confidence: 99%
“…1). Less common manifestations include, among others: jaw claudication [21], gastroparesis and intestinal pseudo-obstruction, polyarthralgia [22], muscle pseudohypertrophy [23], xerostomia [24] and alopecia [25]. The two most common involved organs are the kidneys and the heart (60-80% of patients in most reports).…”
Section: Recognitionmentioning
confidence: 99%
“…However, advanced organ involvement, especially cardiac involvement, occasionally limits the indications for chemotherapy and results in a poor outcome (5). We previously reported that the liver is the third most frequently affected organ after the kidney and heart in systemic AL amyloidosis (6), and clinical problems due to hepatic involvement, such as liver dysfunction and/or hepatic rupture, occasionally prevent patients from receiving effective chemotherapy (7). Therefore, liver transplantation (LT) has been applied in some patients with dominant hepatic amyloidosis as a potential therapeutic option.…”
Section: Introductionmentioning
confidence: 99%